Cross-National Analysis of Adolescent Mental Health : Implications for Global Educational Policies - Rosyidah Alfitri; Rani Safitri; Nila Widya Keswara (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
This study presents a cross-national analysis of adolescent mental health and academic stress to explore their interrelations and broader implications for global educational policies. Using data from Bangladesh, Gambia, and Indonesia, the research examines how academic expectations, pressure to perform, and school environments affect students' psychological well-being in diverse cultural, educational, and socioeconomic contexts. The study identifies significant patterns and disparities in mental health outcomes, revealing that stress levels and psychological challenges vary significantly between countries. In Bangladesh, medical students face a critical mental health burden, with high levels of anxiety, stress, digital addiction, and sleep deprivation being common issues. This situation underscores the pressing need for mental health interventions in the education sector, particularly within high-pressure fields such as medical studies. Conversely, in Gambia, there has been a notable increase in inpatient mental health admissions, suggesting a growing awareness of mental health issues and improved access to institutional care. However, the decline in community-based mental health services presents a critical challenge, as these services are essential for sustainable mental health support outside of hospital settings. In Indonesia, while academic stress is prevalent, the focus has been on improving institutional care and psychological support for students, yet there remains a gap in addressing stressors within the school environment. This study emphasizes the urgent need for inclusive, student-centered educational reforms that prioritize mental health support systems and advocate for the integration of mental health services into educational settings. The findings suggest that global educational policies must consider these country-specific challenges and trends in order to create more balanced academic environments that foster both mental well-being and academic success